PERSPECTIVE HADHANAH CONCEPT ANALYSIS STUDY LAW NUMBER 23 OF 2002 ABOUT CHILD PROTECTION - Iqbal, M. (Journal of Higher Education and Academic Advancement, 2026)
Objective:  The purpose of this writing is to analyze hadhanah from the perspective of Law Number 23 of 2002 concerning child protection. Method: The writing of this research is based on library research, namely using library materials as the main data source. Results: There is no law that explicitly and clearly regulates the obligation of child custody to be given to the biological mother or biological father after a divorce. In Law Number 23 of 2002 concerning Child Protection, Article 3 states that child protection aims to ensure the fulfillment of children's rights so that they can live, grow, develop, and participate optimally in accordance with human dignity and dignity, and receive protection from violence and discrimination, in order to realize Indonesian children who are qualified, have noble morals, and are prosperous. There are various reasons that may make parents unable or unwilling to provide for their children. Some common causes or factors that cause parents not to fulfill their obligations to their children include economic factors, personal relationships, or other legal problems. Parenting has a very urgent role in shaping children's development and well-being. One of these urgencies is the formation of children's character so that they become children who are useful for their nation and state. Novelty: Every child has the right to receive health services and social security according to their physical, mental, spiritual and social needs. Fulfillment of children's basic rights is an integral part of implementing the fulfillment of human rights.